A Meta-Analysis of Microbial Therapy Against Metabolic Syndrome: Evidence From Randomized Controlled Trials - Pan, Binhui; Liu, Xiujie; Shi, Jiangmin; Chen, Yaoxuan; Xu, Zhihua; Shi, Dibang; Ruan, Gaoyi; Wang, Fangyan; Huang, Yingpeng; Xu, Changlong (Frontiers in Nutrition, 2021)
Background and aims: Metabolic syndrome (MetS), accompanied with significant intestinal dysbiosis, causes a great public health burden to human society. Here, we carried out a meta-analysis to qualify randomized controlled trials (RCTs) and to systematically evaluate the effect of microbial therapy on MetS. Methods and results: Forty-two RCTs were eligible for this meta-analysis after searching the PubMed, Cochrane, and Embase databases. Pooled estimates demonstrated that treatment with microbial therapy significantly reduced the waist circumference (WC) (SMD = −0.26, 95% CI −0.49, −0.03), fasting blood glucose (FBG) (SMD = −0.35, 95% CI −0.52, −0.18), total cholesterol (TC) (SMD = −0.36, 95% CI −0.55, −0.17), low-density lipoprotein cholesterol (LDL-C) (SMD = −0.42, 95% CI −0.61, −0.22), and triacylglycerol (TG)(SMD = −0.38, 95% CI −0.55, −0.20), but increased the high-density lipoprotein cholesterol (HDL-C) (SMD = 0.28, 95% CI.03, 0.52). Sensitivity analysis indicated that after eliminating one study utilizing Bifidobacteriumlactis, results became statistically significant in diastolic blood pressure (DBP) (SMD = −0.24, 95% CI −0.41, −0.07) and in Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) (SMD = −0.28, 95% CI −0.54, −0.03), while the body mass index (BMI) showed significant difference after eliminating one study utilizing oat bran (SMD = −0.16, 95% CI −0.31, −0.01). There was still no significant effect in systolic blood pressure (SBP) and in hemoglobin A1c (HbA1c%). Conclusion: In patients with MetS, the conditioning with microbial therapy notably improves FBG, TC, TG, HDL-C, LDL-C, WC, BMI (except for the study using oat bran), HOMA-IR, and DBP (except for the Study using Bifidobacteriumlactis), however, with no effect in SBP and in HbA1c%.